Mapping floodplain bathymetry in the middle-lower Amazon River using inundation frequency and field control - Ang, Wei Jing (2021)
This paper presents the geomorphic classification and bathymetry (at 100 m) of 12 major floodplains along a 900 km reach of the middle-lower Amazon River (Manaus – Monte Alegre; total floodplain area of 5164 km2), based on the inundation frequency (IF) derived from 36 yr of Landsat data. Using a mathematical relationship between IF and surveyed depth at the Curuai floodplain in June 2004, this IF-depth model is applied across floodplains of the middle-lower Amazon to estimate bathymetry. The applicability of the model is justified by similar grain size distribution (dominantly silt and clay) of sediment in the surface water of floodplain lakes (the main materials constructing the floodplains), as well as a hydrogeomorphic classification of this reach: seven floodplains lying on the alluvial plain dominated by the Amazon-flood pulse (Type I), three floodplains incised in valleys dominated by sediment-poor upland tributaries (Type II) and two floodplains of mixed types. This classification is used to distinguish the sensitivity of floodplains to the IF-depth model, where Type I floodplains of higher sensitivity provide a more accurate depth estimation. The bathymetry for both types is validated with field survey data across eight floodplains (covering over 200 km survey distance) collected in June – July 2016 and adjusted by the difference between mean June 2004 and June/July 2016 water level. Correlation coefficients of 0.87 (Type I) and 0.94 (Type II) indicate a strong relationship between estimated and measured depth for both floodplain types, while the root mean square error of 1.03 m (Type I) and 1.02 m (Type II) suggest that bathymetry is estimated to around 1 m error, equivalent to 10.9% and 10.8% of maximum water level variability, respectively. We offer the first field-validated and complete bathymetry map for the middle-lower Amazon River with accuracy that can be used to evaluate the role of floodplains in influencing biodiversity, sedimentation, flood control and biogeochemical cycling.